Employment Protection Legislation, Capital Investment and Access to Credit: Evidence from Italy. (30th June 2015) - Cingano, Federico; Leonardi, Marco; Messina, Julián; Pica, Giovanni
Abstract : This article estimates the causal impact of dismissal costs on capital deepening and productivity, exploiting a reform that introduced unjust‐dismissal costs in Italy for firms below 15 employees, leaving firing costs unchanged for larger firms. We show that the rise in firing costs induced an increase in the capital‐labour ratio and a decline in total factor productivity in small firms relative to larger firms. Our results indicate that capital deepening was more pronounced at the low‐end of the capital distribution – where the reform hit arguably harder – and among firms endowed with a larger amount of liquid resources. We also find that stricter Employment Protection Legislation (EPL) raised the share of high‐tenure workers, which suggests a complementarity between firm‐specific human capital and physical capital in moderate EPL environments.